2000
DOI: 10.1093/carcin/21.4.663
|View full text |Cite
|
Sign up to set email alerts
|

Increased salivary acetaldehyde levels in heavy drinkers and smokers: a microbiological approach to oral cavity cancer

Abstract: The pathogenetic mechanisms behind alcohol-associated carcinogenesis in the upper digestive tract remain unclear, as alcohol is not carcinogenic. However, there is increasing evidence that a major part of the tumour-promoting action of alcohol might be mediated via its first, toxic and carcinogenic metabolite acetaldehyde. Acetaldehyde is produced from ethanol in the epithelia by mucosal alcohol dehydrogenases, but much higher levels derive from microbial oxidation of ethanol by the oral microflora. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
242
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(256 citation statements)
references
References 29 publications
11
242
0
3
Order By: Relevance
“…19 Furthermore, in vitro acetaldehyde production by mouthwashings from oropharyngolaryngeal cancer patients has been shown to be significantly higher than that of the control patients, 11 and the production of acetaldehyde in saliva from ethanol is markedly increased in smokers and heavy drinkers. 38 To prevent the harmful effects of ethanol-derived acetaldehyde, beside being an abstainer, we show that two-thirds of acetaldehyde can be trapped in the saliva with slowly and continuously released L-cysteine. Thiol compounds, such as cysteine, are known to be able to protect against acetaldehyde toxicity.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…19 Furthermore, in vitro acetaldehyde production by mouthwashings from oropharyngolaryngeal cancer patients has been shown to be significantly higher than that of the control patients, 11 and the production of acetaldehyde in saliva from ethanol is markedly increased in smokers and heavy drinkers. 38 To prevent the harmful effects of ethanol-derived acetaldehyde, beside being an abstainer, we show that two-thirds of acetaldehyde can be trapped in the saliva with slowly and continuously released L-cysteine. Thiol compounds, such as cysteine, are known to be able to protect against acetaldehyde toxicity.…”
Section: Discussionmentioning
confidence: 87%
“…38 Moreover, poor oral hygiene, heavy alcohol drinking and smoking may contribute to the individual risk of upper GI-tract cancers by increasing the acetaldehyde levels in the oral cavity. 38 Our buccal drug formulation slowly releases cysteine to the oral cavity. Thus, it enables a continuous concentration of cysteine in the mouth during microbially mediated ethanol oxidation and acetaldehyde challenge.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, increased ACH levels in saliva have been associated with increased risk for upper aerodigestive tract cancer [35], which was the seventh most common cancer in Japan in 2011 with one million newly diagnosed cases annually worldwide [6,7]. Increased ACH levels in saliva after ethanol consumption are suggested to be due to oxidation of alcohol by the oral microbiota [8,9]. …”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] They all associate with increased acetaldehyde (ACH) levels in saliva, and there is strong evidence supporting the role of ACH as a common dominator. [13][14][15][16][17][18] The mechanism leading to increased ACH levels in saliva after alcohol consumption is local microbial ACH production, i.e. the oxidation of salivary ethanol (EtOH) to ACH by microbial alcohol dehydrogenase (ADH)-enzyme.…”
mentioning
confidence: 99%
“…the oxidation of salivary ethanol (EtOH) to ACH by microbial alcohol dehydrogenase (ADH)-enzyme. [15][16][17] Previous studies have shown that Candida albicans can produce significant amounts of carcinogenic ACH in clinically relevant EtOH concentrations. 19 It has been demonstrated that polyamines are able to facilitate the formation of mutagenic DNA-adducts in biologically relevant ACH concentrations (50-100 lM).…”
mentioning
confidence: 99%